The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1177/02692163231154300
|View full text |Cite
|
Sign up to set email alerts
|

What does ‘good’ palliative care look like for children and young people? A qualitative study of parents’ experiences and perspectives

Abstract: Background: Worldwide, around 21 million children would benefit from palliative care and over 7 million babies and children die each year. Whilst provision of paediatric palliative care is advancing, there major gaps between what should be done, and what is being done, in clinical practice. In 2017, the National Institute for Health and Care Excellence (NICE) introduced a quality standard, to standardise and improve children’s palliative care in England. However, there is little evidence about what good experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Even in Western countries with a relatively long history of palliative care, many parents experience difficulties despite a well-established system. Fields et al 22 observed that parents from the United Kingdom experienced an excessive burden as caregivers owing to the absence of a coordinator who oversees and leads care. A Dutch study by Kochen et al 23 showed that although parents want to faithfully fulfill their role as parents for the limited time their children have, the pain of their child's imminent death affects their role as caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Even in Western countries with a relatively long history of palliative care, many parents experience difficulties despite a well-established system. Fields et al 22 observed that parents from the United Kingdom experienced an excessive burden as caregivers owing to the absence of a coordinator who oversees and leads care. A Dutch study by Kochen et al 23 showed that although parents want to faithfully fulfill their role as parents for the limited time their children have, the pain of their child's imminent death affects their role as caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Successful palliative care is characterised by trusted cooperation between families and professionals, as this enables parents to be more than just caregivers for their sick children (11). For children needing palliative care, the municipal coordinator should ensure that the children and their families receive active and comprehensive care tailored to their unique needs (12).…”
Section: Introductionmentioning
confidence: 99%